Electron–phonon interaction and ultrafast photoemission from doped monolayer MoS2. Issue 41 (13th October 2022) - Nayyar, Neha; Le, Duy; Turkowski, Volodymyr; Rahman, Talat S.
Abstract : We present results of combined density functional theory and many-body theory analysis of the effect of electron–phonon coupling on photoluminescence and ultrafast response of electron doped monolayer MoS2 . Abstract : We have examined the effect of electron–phonon coupling on photoluminescence and ultrafast response of electron doped monolayer MoS2, using a combination of density functional theory, time dependent density functional theory, and many-body theory. For small doping (∼1–3%) of interest here, the electron–phonon coupling parameter is modest (∼0.1–0.2) but its effect on the emissive properties and response of the system to femtosecond (fs) laser pulses is striking. We find an ultrafast (fs) relaxation of the electronic subsystem as well as a high fluence of visible light emission induced by electron phonon interaction. Together with high carrier mobility, these features of monolayer MoS2 may be relevant for optoelectronic technologies.